Modelamento CFD tridimensional da combustão de finos de carvão vegetal e mineral sob condições de um alto-forno a coque - Diego Silva de Deus Vieira (2020)
Blast furnace is the main metallurgical reactor used to produce hot metal. Due to the environmental pressures to reduce fossil fuels consumption and CO2 emissions, it is necessary to develop new technologies in the ironmaking process. However, since there are many technical difficulties to acquire data from inside the reactor, physical and mathematical models appear as very attractive alternatives in blast-furnace studies, especially in the combustion zone. Nowadays, there are a considerable number of computational models able to simulate pulverized coal combustion. Nevertheless, there are just a few works aiming to predict the combustion of charcoal. This work aims to analyze different forms of O2 enrichment (coaxial and conventional) and to investigate the combustion efficiency for mixtures formed by coals and charcoals injected in a blast furnace raceway. Through a 3D computational fluid-dynamic model developed and validated (through data in the literature) using the commercial software ANSYS-CFX, which is capable of simulating the combustion of different coals. Thus, as possible implications of this present study, greater energy efficiency for the injected fuels can be reached, as well as a consequent reduction in the consumption of coke and in the production costs. And also, due to the greater use of charcoal, which is a renewable raw material, reductions in CO2 emissions can be achieved. It was observed that O2 enrichment by the coaxial lance becomes detrimental to the coal combustibility beyond 3%, in which the flow in the lance is greater than 12Nm3 /h. As a result, it slows down the heating process of the particles. The importance of coal granulometry and volatile matter content in the combustion process became evident. Coals with smaller particle sizes and higher volatile matter contents tend to have higher combustibility indexes. From the simulations with coal and charcoal blends, it was observed that blends composed by 25% of charcoal present improvements in combustibility.